Analisis Penerapan Metode Association Rule Mining Untuk Transaksi Penjualan di Toko Bangunan Dengan Algoritma Apriori - Anggraini, Diah; Sanjaya, Ucta Pradema; Sa’ida, Ita Aristia (SINTECH (Science and Information Technology) Journal, 2022)
In improving the quality of service to customers, UD. Lasmi Jaya store is asked to be able to handle problems that often arise, among others, lack or absence of (out of stock) stock of building goods that are very popular, less strategic layouts, assist in decision making to develop marketing strategies and promote better products and more. Therefore, in this problem, there must be utilization of sales transaction data for processing using a priori algorithms so that it can provide new knowledge that can be utilized by shop owners. From the results of research that has been carried out from 300 sales transaction data from January 1, 2022 - June 30, 2022 with a comparison of a minimum transaction of 15 or a minimum of 5% support and a minimum of 40% confidence with a minimum of 12 transactions or a minimum of 4% support and a minimum of 30% confidence, associations the final results found were more at least 12 transactions or minimum support 4% and minimum confidence 30% because if the minimum support value and minimum confidence value were lower then the association value found would be more, so for determining stock of goods or layout of goods or as promotion and others so that it will make it easier for the owner to manage their sales so that they can grow and provide satisfaction